Oxygen consumption, heart rate and the electrocardiogram of pigs during exertion - Howard H Erickson; F M Faraci; S C Olsen (Kansas Agricultural Experiment Station Research Reports, 1983)
Pigs were exercised for 5 minutes at five different treadmill speeds (1.0-1.8 sec^-1 ) (3° incline), while oxygen consumption (MO2), carbon dioxide production (MCO2), and the electrocardiogram (ECG) were continuously recorded. Data were taken at rest, during exercise, and at 2, 5, 15, and 30 minutes after exercise. MO2, MCO2, and heart rate (HR) showed progressive increases with increasing treadmill speed. The respiratory exchange ratio (R) increased during exercise and approached 1.0, but peak values were seen shortly after exercise. A high correlation between HR and MO2 was found in these animals. Prominent increases in T-wave amplitude of the ECG were associated with exercise and early recovery.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Oxygen; Heart rate; Electrocardiogram; Exertion